Health assets in a global context: a systematic review of the literature. Issue 2 (3rd February 2019) - Van Bortel, Tine; Wickramasinghe, Nuwan Darshana; Morgan, Antony; Martin, Steven
Abstract : Objective: To provide an up-to-date overview of health assets in a global context both from a theoretical perspective and its practical applications to address health inequalities and achieve sustainable health. Design: A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data sources: A comprehensive search, including 10 electronic bibliographic databases and hand searches, was undertaken to capture the wide range of terms associated with 'health assets' and 'asset-based approaches to health'. Eligibility criteria: Any peer-reviewed published and grey literature in English related to 'health assets' or 'assets' in a 'health' context was included without any date, country or study design restrictions and the quality of evidence was appraised according to the Oxford Level of Evidence. Outcomes: A broad consideration of all outcome measures including clinical outcomes, patient-level, community-level and population-level impacts and costs, was adopted. Results: 478 publications were included. Health assets were researched in 40 countries, predominantly in the West such as the USA and the UK. A number of broad health assets were identified including community and individual assets. Even though research was conducted in a number of different settings, most occurred in the community, clinical, care or educational settings. A wide variety of interventions and approaches were implemented, most commonly related to education and/or training, asset mapping or asset approaches. Conclusions: Globally, authors most often referred to general 'health assets', 'assets' or some form of 'community asset' in relation to health. Overall, the idea of health assets is framed within a positive paradigm focusing on health creation rather than curative approaches. The sustained credibility of the global 'health assets' literature depends on future research on definitional, theoretical and evaluative issues in order to convince policy-makers and service commissioners of its necessity and added value to the traditional deficit approach.